Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages After One Year The Commons Debate of 4th June, 1946, showed how sombre the situation had become, as a result of endless wrangling at the Council of Foreign Ministers and at the United Nations Security Council. Mr. Bevin would give Russia one more chance on the 15th June! If the four Foreign Ministers could not agree then Britain would demand a Conference of the 21 Allied countries. That meant making peace with Italy, Austria and Germany, independently of Russia. Mr. Bevin added : "I think Mr. Molotov has been more than unjust in stating that we are trying to expand the British Empire at the expense of Italy and Ethiopia, and consolidating what he calls the Imperialistic position of Great Britain in the Mediterranean and Red Sea." Yet in the same speech he told the House he proposed to claim British trusteeship for Cyrenaica, because we gave a pledge to the Senussi there that they would never be restored to Italian rule. Yet the Arabs (and the Senussi are Arabs) do not want foreign rule in North Africa. And Herbert Morrison agreed to British troops leaving Egypt "reluctantly," because such a step might weaken the Empire. The Labour Government cannot have both Imperialism and Peace. If they cling to the Empire, they will clash with one rival Great Power, Russia, and only get the other's, U.S.A.'s, help, at the price of obeying her orders. We may consider Russia's unconciliatory attitude the consequence — as Mr. Bevin does — of a belief that her safety could only be maintained when the rest of the world had adopted the Soviet system. Or we may think — as C.W. does — that it stems from an exaggerated desire for security and a fear of other nations pathological in its intensity ; for the world-revolutionary fervour of Lenin's day has long gone. But war-damaged Russia cannot be a dangerous rival in either case, and should not be reviled as such. This review of Labour's first year shows us, surely, that the Government's policy in international affairs should be reversed. There must be no more forcible efforts to keep down colonial peoples. It must be recognised that British "interests" do not mean British investments abroad — though the Foreign Office angrily protested, recently, that a big British firm was not getting sufficient compensation when its properties were nationalised in Czecho-Slovakia. Peace is Britain's greatest interest, for an atomic war would destroy us. A Peace Policy means Socialism at home and co-operation with democratic and socialist governments and movements abroad, coupled with persistent efforts to mediate between the U.S.A. and the U.S.S.R. and a firm refusal to be linked solely with either. 9 15X/2/98/21